Entrepreneurial intention and its influencing factors : a study among UUM undergraduate business students - Nur'arifah, Mohd Rashid (2017)
The purpose of this study is to examine the relationship between risk taking propensity, need for achievement, entrepreneurship education and entrepreneurial intention among UUM undergraduate business students. 350 questionnaires were distributed to the respondents which consist of UUM School of Business Management (SBM) undergraduate students. A total of 338 questionnaires were returned, but only 335 questionnaires were useable for the further analysis. The data collected through this survey was analyzed by using the Statistical Package for Social Science (SPSS) version 22. This study used convenience sampling method where the data collected from population members who are conveniently available to participate in the study. The descriptive analysis was used to determine the respondents‟ profile. Findings of this study revealed that two of the variables, risk taking propensity and need for achievement have positive significant relationship towards entrepreneurial intention. Meanwhile, another one variable, entrepreneurship education has no significant relationship towards entrepreneurial intention. This study could assist in developing, improving and implementing an effective entrepreneurship education. Moreover, it can aid government and also societies in generating the economy through the entrepreneurial activities. Finally, this study proposes several recommendations for future research.